Localization of pyruvate:NADP+ oxidoreductase in sporozoites of Cryptosporidium parvum - Ctrnacta, Vlasta; Ault, Jeffrey G; Stejskal, Frantisek; Keithly, Janet S (The Journal of eukaryotic microbiology, 2006)
Cryptosporidium parvum contains a unique fusion protein pyruvate:NADP+ oxidoreductase (CpPNO) that is composed of two distinct, conserved domains, an N-terminal pyruvate:ferredoxin oxidoreductase (PFO) and a C-terminal cytochrome P450 reductase (CPR). Unlike a similar fusion protein that localizes to the mitochondrion of the photosynthetic protist Euglena gracilis, CpPNO lacks an N-terminal mitochondrial targeting sequence. Using two distinct polyclonal antibodies raised against CpPFO and one polyclonal antibody against CpCPR, Western blot analysis has shown that sporozoites of C. parvum express the entire CpPNO fusion protein. Furthermore, confocal immunofluorescence and transmission electron microscopy confirm that CpPNO is localized within the cytosol rather than the relict mitochondrion of C. parvum. The distribution of this protein is not, however, strictly confined to the cytosol. CpPNO also appears to localize posteriorly within the crystalloid body.
Keywords: sporozoiti; konfokální mikroskopie; fluorescenční mikroskopie; Cryptosporidium parvum; western blotting; Sporozoites; Euglena gracilis; Pyruvate Synthase; cytosol; protozoální proteiny; ketonoxidoreduktasy; organely; Cytosol; Microscopy, Confocal; Blotting, Western; Animals; Organelles; Microscopy, Fluorescence; Microscopy, Electron, Transmission; NADPH-Ferrihemoprotein Reductase; zvířata; pyruvátsynthasa; NADPH-cytochrom c-reduktasa; Protozoan Proteins; transmisní elektronová mikroskopie; Ketone Oxidoreductases